1961
DOI: 10.1128/jb.82.6.808-814.1961
|View full text |Cite
|
Sign up to set email alerts
|

SPHEROPLASTS OF THE YEASTCANDIDA UTILIS

Abstract: and properties of spheroplasts of the yeast Candida utilis, produced by digestion of the cell walls with snail gut juice (Helix pomnatia) in isotonic medium, were studied by l)hase, interference, and ultraviolet microscopy, and tracer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
23
0

Year Published

1969
1969
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 10 publications
(3 reference statements)
4
23
0
Order By: Relevance
“…An increased yield of protoplasts was also obtained from cells grown in media supplemented with sulfur amino acids or other sulfhydryl compounds. Similar results have earlier been obtained with fungi after the addition of sulfur amino acids (Killick 1971, Svilha et al, 1961 and mercaptoethanol (Duell et al, 1964) to the culture medium. Since both the sulfur amino acids methionine and cysteine and other sulfhydryl compounds showed a great positive effect on •protoplast yield but other amino acids and reducing agents without sulfhydryl groups were less effective or inactive, it seems likely that the sulfhydryl group are responsible for the positive effects.…”
Section: Discussionsupporting
confidence: 87%
“…An increased yield of protoplasts was also obtained from cells grown in media supplemented with sulfur amino acids or other sulfhydryl compounds. Similar results have earlier been obtained with fungi after the addition of sulfur amino acids (Killick 1971, Svilha et al, 1961 and mercaptoethanol (Duell et al, 1964) to the culture medium. Since both the sulfur amino acids methionine and cysteine and other sulfhydryl compounds showed a great positive effect on •protoplast yield but other amino acids and reducing agents without sulfhydryl groups were less effective or inactive, it seems likely that the sulfhydryl group are responsible for the positive effects.…”
Section: Discussionsupporting
confidence: 87%
“…The importance of the strain, growth conditions, and the physiological state of the harvested cells in determining the sensitivity of yeast cells to the digestive enzymes has also been emphasized (25). Svihla et al (23) reported that Candida utilis cultured in a medium supplemented with sulfur amino acids formed spheroplasts by the enzymatic action of snail extract more readily than nonsupplemented cultures. The sulfonium compound, S-adenosylmethionine (AM) occurred in concentrations ranging from 0.3 to 2.0 umoles per g (wet weight) of nonsupplemented yeast cells (23).…”
mentioning
confidence: 99%
“…Svihla et al (23) reported that Candida utilis cultured in a medium supplemented with sulfur amino acids formed spheroplasts by the enzymatic action of snail extract more readily than nonsupplemented cultures. The sulfonium compound, S-adenosylmethionine (AM) occurred in concentrations ranging from 0.3 to 2.0 umoles per g (wet weight) of nonsupplemented yeast cells (23). In the sulfur amino acid-supplemented medium, however, the AM concentration was elevated to 20 to 30 ,umoles per g (wet weight) of cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations